2015
DOI: 10.1371/journal.pone.0131615
|View full text |Cite
|
Sign up to set email alerts
|

The Oral Bacterial Communities of Children with Well-Controlled HIV Infection and without HIV Infection

Abstract: The oral microbial community (microbiota) plays a critical role in human health and disease. Alterations in the oral microbiota may be associated with disorders such as gingivitis, periodontitis, childhood caries, alveolar osteitis, oral candidiasis and endodontic infections. In the immunosuppressed population, the spectrum of potential oral disease is even broader, encompassing candidiasis, necrotizing gingivitis, parotid gland enlargement, Kaposi’s sarcoma, oral warts and other diseases. Here, we used 454 py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 38 publications
1
41
3
Order By: Relevance
“…The results of the present study are in conflict with those of Goldberg et al, , Noguera‐Julian et al, and Starr et al, . The reason for this apparent conflict could lie in the fact that different populations were studied.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of the present study are in conflict with those of Goldberg et al, , Noguera‐Julian et al, and Starr et al, . The reason for this apparent conflict could lie in the fact that different populations were studied.…”
Section: Discussioncontrasting
confidence: 99%
“…A number of authors have studied the oral microbiota of HIV‐1‐infected individuals using gene amplicon sequencing (Beck et al, ; Dang et al, ; Goldberg et al, ; Kistler, Arirachakaran, Poovorawan, Dahlen, & Wade, ; Li et al, ; Noguera‐Julian et al, ; Presti et al, ; Starr et al, ); however, only two papers have been published regarding the oral microbiome of HIV‐1‐infected children (Goldberg et al, ; Starr et al, ). These studies were carried out with HIV‐1‐infected children from the United States, by the use of 454 pyrosequencing (Goldberg et al, ) or Illumina platform on a MiSeq (Starr et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A small study in children with only 5 HIV-negative controls found no evident differences in the oral microbiome composition between well-controlled HIV-positive and HIV-negative children. [17] In comparison, 15 subjects with AIDS attending HIV clinics in China showed significant increases in several bacteria, and a distinct salivary bacterial profile between necrotic and chronic PD. [18] Using a microbial microarray, there were significant differences in the salivary bacterial composition between HIV-positive subjects before and after ART initiation and between them and HIV-negative adults.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, our knowledge of opportunistic pathogens in relation to HIV-related proximal gut problems is rather limited, and clinical signs and symptoms alone rarely suggest a specific etiology. Besides the distal gut microbiome, high-throughput sequencing has been used to examine the effects of HIV infection on the microbiomes in the vagina [2931], lung [32], mouth [33, 34], Semen [35], and anus [36] as well as in normally sterile body sites such as the brain [37] and blood [38, 39], but not in the proximal gut. Unlike its distal counterpart, the status of microbiome in the proximal gut in HIV infection was only examined recently by analysis of gastric juice samples from only two HIV patients [40].…”
Section: Introductionmentioning
confidence: 99%